Surface modification of 5083 aluminum-magnesium induced by marine microorganisms - Jaume, Julien (2022)
ABSTRACT: The influence of microorganisms from a salt marsh in the surface modification of 5083 aluminum alloy (Al-Mg) in seawater was evaluated. An immersion test performed for 50 days in biotic and abiotic conditions, with electrochemical monitoring and surface/cross-section characterization by SEM/EDX and TEM after exposure, showed that microorganisms induced the formation of a homogenous layer on the Al-Mg surface. This layer, which proved to be composed of a doublestructure: a dense, amorphous inner layer and a more porous outer layer, was demonstrated to influence the corrosion resistance of the Al-Mg alloy in seawater.